Regulation of Interleukin 3 mRNA Expression in Mast Cells Occurs at the Posttranscriptional Level and is Mediated by Calcium Ions - Wodnar-Filipowicz, Aleksandra; Moroni, Christoph (Proceedings of the National Academy of Sciences - PNAS, 1990)
Interleukin 3 (IL-3) is transiently produced by murine bone marrow-derived mast cells in response to antigen stimulation of the high-affinity immunoglobulin E receptors. We have studied the postreceptor signaling pathways involved in regulating expression of the IL-3 gene in the murine mast cell line PB-3c. Large amounts of IL-3 mRNA accumulated after exposure of cells to calcium ionophore A23187, a reagent that increases intracellular Ca2+. Phorbol 12-myristate 13-acetate, which stimulates protein kinase C, did not induce IL-3 mRNA accumulation, although it did potentiate the effect of A23187. Nuclear run-on analysis showed that the IL-3 gene is constitutively transcribed in unstimulated cells and that treatment with A23187 and/or phorbol ester has no influence on its transcription rate. The effect of A23187 was found to be due to stabilization of the IL-3 mRNA. In cells maintained in the presence of A23187 the IL-3 mRNA was stable during 3 hr of incubation with actinomycin D, whereas removal of A23187 under the same conditions resulted in rapid degradation of the mRNA. These results indicate that control of expression of the IL-3 gene in mast cells is primarily at the posttranscriptional level and that the Ca2+-dependent signal-transduction pathway plays an important role in this process. Synthesis of granulocyte/macrophage colony-stimulating factor mRNA in response to A23187 and phorbol ester was found to be subject to both transcriptional and posttranscriptional regulation.